Social Media User Students’ Academic Procrastination - Muslikah, Muslikah; Mulawarman, Mulawarman; Andriyani, Ayu (Psikopedagogia, 2018)
This study aimed to find out the relationship between students’ academic procrastination with the intensity of social media use. This study employed quantitative approach with correlational design. The subject of the study was 419 students of the State University of Semarang from various faculties, they were selected by using random sampling technique. The data collection instrument of the study were social media use scale and academic procrastination scale. The data were analyzed using product moment. The result of the study showed coefficient correlation (r) of -0.344 and p = 0.000 (p < 0.05). This means that there is positive and significant relationship between academic procrastination and social media use intensity. The higher the academic procrastination, the higher the intensity of social media use, and vice versa. The result of the study can provide contribution to the school counselor as a prediction and initial data before providing guidance and counseling service on academic procrastination and being wise in social media.Keywords: